REVISITED CHARACTERISTICS OF RUSSIAN ECONOMY TRANSITION TO SUSTAINABILITY - Vladimir N. Kurdyukov (Advanced Engineering Research)
Problems of the Russian economy in the perspective of the transition to the sustainable development are considered. Terms of sustainability security are described.